Synthesis, crystal structure, and catalytic activity of bridged-bis(N-heterocyclic carbene) palladium(II) complexes in selective Mizoroki-Heck cross-coupling reactions - Mansour, Waseem; Suleiman, Rami; Iali, Wissam; Fettouhi, Mohammed; El Ali, Bassam (Polyhedron, 2021)
Three propylene bridged bis(N-heterocyclic carbene)palladium(II) complexes were synthesized and the subject of a spectroscopic, structural, computational and catalytic investigation. These bis(NHC)PdBr2 complexes were evaluated in Mizoroki-Heck coupling reactions of aryl bromides with styrene or acrylate derivatives and showed high catalytic efficiency to produce diarylethenes and cinnamic acid derivatives. [Display omitted] A series of three 1,3-propanediyl bridged bis(N-heterocyclic carbene)palladium(II) complexes (Pd-BNH1, Pd-BNH2, and Pd-BNH3), with + I effect order of the N-substituents of the ligand (isopropyl > benzyl > methoxyphenyl), was the subject of a spectroscopic, structural, computational and catalytic investigation. The bis(NHC)PdBr2 complexes were evaluated in Mizoroki-Heck coupling reactions of aryl bromides with styrene or acrylate derivatives and showed high catalytic efficiency to produce diarylethenes and cinnamic acid derivatives. The X-ray structure of the most active palladium complex Pd-BNH3 shows that the Pd(II) center is bonded to the two carbon atoms of the bis(N-heterocyclic carbene) and two bromide ligands in cis position, resulting in a distorted square planar geometry. The NMR data of Pd-BNH3 are consistent with a single chair-boat rigid conformer in solution with no dynamic behavior of the 8-membered ring palladacycle in the temperature range 25–120 °C. The catalytic activities of three Pd-bridged bis(NHC) complexes in the Mizoroki-Heck cross-coupling reactions were not found to have a direct correlation with +I effect order of the N-substituents of the ligand. However, a direct correlation was found between the DFT calculated absolute softness of the three complexes with their respective catalytic activity. The highest calculated softness, in the case of Pd-BNH3, is expected to favor the coordination steps of both the soft aryl bromides and alkenes in the Heck catalytic cycle.